Advancing the Agenda of the Confederation of Trade Unions on the Prevention of Sexual Violence in the World of Work in Indonesia - Sigiro, Atnike Nova (Yayasan Jurnal Perempuan, 2021)
This article was formulated based on interviews with 5 (five) trade union confederations from a number of confederations in Indonesia, namely: Konfederasi Serikat Pekerja Nasional (KSPN), Konfederasi Sarikat Buruh Muslimin Indonesia (KSarbumusi), Konfederasi Serikat Buruh Seluruh Indonesia (KSBSI), Konfederasi Serikat Pekerja Indonesia (KSPI), and Konfederasi Kongres Aliansi Serikat Buruh Indonesia (KKASBI). This article seeks to explore the efforts made by the trade union confederation in promoting gender equality - specifically in advancing the agenda for the prevention and elimination of sexual violence in the world of work. This article was compiled based on research with a qualitative approach, with data collection methods through interviews and literature studies. The results of this study found that the confederations interviewed had already set up internal structures that have specific functions on issues related to gender equality, gender-based violence, and women’s empowerment; although still limited and on ad-hoc basis. This research also finds that the role of the trade union confederation is particularly prominent in advocating policies related to sexual violence and gender-based violence in the world of work, such as advocating the Bill on the Elimination of Sexual Violence, and the ratification of the ILO Convention No. 190 on Violence and Harassment.